2011
DOI: 10.1242/jeb.055566
|View full text |Cite
|
Sign up to set email alerts
|

In ovo thyroxine exposure alters later UVS cone loss in juvenile rainbow trout

Abstract: a thyroid hormone) induces precocious SWS1 downregulation and UVS cone degeneration, whereas TH attenuation via propylthiouracil (PTU) delays SWS1 downregulation and UVS cone loss, suggesting that endogenous T4 initiates these processes naturally during development (Browman and Hawryshyn, 1992;Browman and Hawryshyn, 1994 Accepted 17 March 2011 SUMMARY Thyroid hormones (THs) play a vital role in vertebrate neural development, and, together with the beta isoform of the thyroid hormone receptor (TR), the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Our results are consistent with published reports showing that photoreceptors, optic primordia, optic nerve development, and opsin expression are influenced by thyroid function (Gamborino et al, 2001;Gan and Novales Flamarique, 2010;Fischer et al, 2011;Pinazo-Duran et al, 2011;Raine et al, 2011). Previous studies have shown that treatment with phenylthiourea can decrease zebrafish dorsal retina and lens due to its effects on thyroid peroxidase .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with published reports showing that photoreceptors, optic primordia, optic nerve development, and opsin expression are influenced by thyroid function (Gamborino et al, 2001;Gan and Novales Flamarique, 2010;Fischer et al, 2011;Pinazo-Duran et al, 2011;Raine et al, 2011). Previous studies have shown that treatment with phenylthiourea can decrease zebrafish dorsal retina and lens due to its effects on thyroid peroxidase .…”
Section: Discussionsupporting
confidence: 93%
“…In salmonid fish, TR genes have been detected in various organs (brain, intestine, gill, liver, muscle, kidney, ovary, skin, etc.) of rainbow trout ( O. mykiss ) ( Jones et al., 2002 ; Raine et al., 2005 , 2011 ), coho salmon ( Harada et al., 2008 ), and Atlantic salmon ( Salmo salar ) ( Marchand et al., 2001 ). However, TR gene expression in the peripheral olfactory system has not been widely studied in vertebrates, including teleost.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility of rainbow trout oocytes and survival to the eyed stage of development were the same or better following storage in Cortland's solution when compared to storage in coelomic fluid or fertilization prior to storage (Goetz & Coffman, 2000). Coelomic fluid has been shown to be an effective delivery medium in this and other studies (Raine et al, 2004, 2011; Raine & Leatherland, 2003), but Cortland's solution provides a logistically simpler medium to use and appears to work quite successfully in this application.…”
Section: Discussionmentioning
confidence: 59%
“…This suggests that this method of exposure is a viable and practical procedure to study in ovo developmental effects of PFAS on large‐bodied species of fish. This exposure method has been used previously to deliver thyroid hormones, cortisol, and bisphenol A into prefertilization rainbow trout oocytes using coelomic fluid as the exposure medium (Aluru et al, 2010; Birceanu et al, 2015; Coffin et al, 2012; M. Li et al, 2010; Raine et al, 2004, 2011; Raine & Leatherland, 2003). Coelomic fluid is difficult to obtain in quantity, and its association with the oocytes makes it difficult to prepare treatment solutions in advance of an experiment.…”
Section: Discussionmentioning
confidence: 99%